Tribological characteristics of multiwalled carbon nanotubes and boron carbide particles reinforced Al2024 matrix composites. (2018) - Zakaulla, Mohamed; Arjun, R.; Ahmed Khan, Muzakkir; Hussein Khan, Izhar; Pasha, Nadeem
Abstract: Wear and friction behavior of Al2024 monolithic alloy reinforced with 10wt% B4 C particles and MWCNTs varied in 1wt% and 2wt% was investigated. The hybrid Al2024 composite were fabricated using stir casting technique. Experiment was performed using pin-on-disk wear testing machine against a steel disk of hardness Rc 60 under a load of 10N, 20N and 30N with sliding speed of 0.84m/sec. The tribological test results indicated that Al2024-10wt% B4 C + 2%MWCNTs displayed lower friction coefficient and wear rate compared to Al2024-10wt% B4 C + 1%MWCNTs, Al2024-10wt% B4 C composite and Al2024 alloy. The worn surfaces were examined using high resolution scanning electron microscope.